Concentration Dependent Effect of Plant Root Exudates on the Chemosensory Systems of Pseudomonas putida KT2440 - López-Farfán, Diana; Reyes-Darias, José A.; Matilla, Miguel A.; Krell, Tino (Frontiers in Microbiology, 2019)
Plant root colonization by rhizobacteria can protect plants against pathogens and promote plant growth, and chemotaxis to root exudates was shown to be an essential prerequisite for efficient root colonization. Since many chemoattractants control the transcript levels of their cognate chemoreceptor genes, we have studied here the transcript levels of the 27 Pseudomonas putida KT2440 chemoreceptor genes in the presence of different maize root exudate (MRE) concentrations. Transcript levels were increased for 10 chemoreceptor genes at low MRE concentrations, whereas almost all receptor genes showed lower transcript levels at high MRE concentrations. The exposure of KT2440 to different MRE concentrations did not alter c-di-GMP levels, indicating that changes in chemoreceptor transcripts are not mediated by this second messenger. Data suggest that rhizosphere colonization unfolds in a temporal fashion. Whereas at a distance to the root, exudates enhance chemoreceptor gene transcript levels promoting in turn chemotaxis, this process is reversed in root vicinity, where the necessity of chemotaxis towards the root may be less important. Insight into KT2440 signaling processes were obtained by analyzing mutants defective in the three cheA paralogous genes. Whereas a mutant in cheA1 showed reduced c-di-GMP levels and impaired biofilm formation, a cheA2 mutant was entirely deficient in MRE chemotaxis, indicating the existence of homologues of the P. aeruginosa wsp and che (chemotaxis) pathways. Signaling through both pathways was important for efficient maize root colonization. Future studies will show whether the MRE concentration dependent effect on chemoreceptor gene transcript levels is a feature shared by other species.